Effect of mix probiotic and vitamin C on growth and some biochemical tests in common carp Cyprinus carpio L: Jamal Khalaf Atiyah AL-Faragi Ali Majhool Kany Al- Thalimy - AL-Faragi, Jamal Khalaf Atiyah (The Iraqi Journal of Veterinary Medicine, 2011)
One hundred and twelve Common carp fish fingerling Cyprinus carpio L.were collected, range between 25-28 gm in weight to study the effect of different concentrations of local probiotic and mixed with Vitamin C in concentration 1g/kg feed on growth performance, blood and biochemical picture. This experiment included 7 groups each group contain 16 fish distributed randomly as follow: Control group (C ) fed diet free vitamin C and probiotic during the period of 60 days and all total protin in feed reach 26% . Group 2(T1) group fed diet contain Vit C (1gm /kg) food. Treated (T2andT3) groups fed diet containing probiotic 4.5&5.5 g/ kg respectively , where as groupsT4,T5 and T6 fed the diets containing Probiotic added at level 4.5,5.5 and 6.5 g/ kg respectively and each mixed with 1 gm\kg Vit C .Results of fish total growth rate were 6.86,9.82,15.00,10.87,17.51,14.60 and 13.51gm, evaluate relative growth rate ,the absolute specific growth rate, food conversion and the protein efficiency ratio . The statistically analysis showed increase significantly(P≤0.05)for T4 in all treatment. While erythrocyte counts was 1.80, 1.88, 1.95, 2.40, 2.00, 2.70, 2.20 and 2.10 ×106 cells\mm3, blood cells counts are 24.40 ,24.60 ,25.80 ,27.00 ,26.00 ,27.96 ,26.60 and 26.20×103cells\mm3, blood haemoglobin was8.40,8.70,9.80, 11.10,10.20,11.90,10.80 and 10.50 gm\100dl, haematocrit value are 27.10 ,27.60 ,28.50 ,29.90 ,29.10 ,30.50 ,29.50 and29.30 % for fish before starting expermint (Z) and C,T1,T2,T3,T4,T5,T6,groups, respectively . Evaluate the enzymatic activity for AST,ALT and ALP in blood serum of fish . The statisticaly analysis showed decrease significantly(P≤0.05) at treatment contain mix probiotic and Vit C but excel T4 inform 70.40,10.40,30.30 I U\ L respectively.Conclusion ,the present studied suggested that the level of probiotic and Vit C (4.5g\kg and Vi C 1gm\kg) used could be improve the performance growth and fish healthy.